Preparation of stable dispersions of layered double hydroxides (LDHs) in nonpolar hydrocarbons: new routes to polyolefin/LDH nanocomposites. - Wang, Q; Zhang, X; Zhu, J; Guo, Z; O'Hare, D (2012)
We report a simple and cost effective solvent treatment method for the synthesis of a stable and transparent dispersion of the hydrophilic layered double hydroxide, [Mg(6)Al(2)(OH)(16)](CO(3)) in non-polar hydrocarbon solvents. This dispersion can be used to make polyolefin/LDH nanocomposites using a simple solvent mixing method.